2022
DOI: 10.1186/s12933-022-01729-9
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance mediates obesity-related risk of cardiovascular disease: a prospective cohort study

Abstract: Background The mechanisms linking obesity to cardiovascular disease (CVD) are still not clearly defined. Individuals who are overweight or obese often develop insulin resistance, mediation of the association between obesity and CVD through the insulin resistance seems plausible and has not been investigated. This study aimed to evaluate whether and to what extend the effect of general and central obesity on cardiovascular disease (CVD) is mediated by insulin resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…All constituents of the CMI are integral components of metabolic syndrome 29,30 , which encompasses central obesity, insulin resistance, dyslipidemia, and hypertension-factors prevalent in cardiovascular diseases and heart failure 31,32 . Obesity, crucial in metabolic syndrome, increases cardiac workload and promotes an in ammatory state harmful to heart function 33 .…”
Section: Discussionmentioning
confidence: 99%
“…All constituents of the CMI are integral components of metabolic syndrome 29,30 , which encompasses central obesity, insulin resistance, dyslipidemia, and hypertension-factors prevalent in cardiovascular diseases and heart failure 31,32 . Obesity, crucial in metabolic syndrome, increases cardiac workload and promotes an in ammatory state harmful to heart function 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies [ 23 25 ], our study re-emphasized that the TyG index was an independent predictor for incident CVD among general middle-aged and elderly populations. Moreover, several recent studies have demonstrated that common risk factors could intertwine and modify their effect on the relationship between the TyG index and CVD [ 13 , 26 , 27 ]. In another study conducted within the CHARLS cohort, Huo et al discovered significant joint and interacting effects of the TyG index and BMI on incident stroke among 8231 Chinese adults, with the TyG index found to mediate more than 50% of the association between BMI and CVD [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the NHANES (1999-2018) database, the major ndings of the present study are as follows: (1) the addition of hyperuricemia to the criteria of MetS contributed to recognize more participants (4.24%) with metabolic risk; (2) both MetS old and MetS new were signi cantly associated with an increased risk of all-cause and CVD mortality; NCEP-ATP III criteria, the most widely used de nition of MetS was conducive to identify individuals with increased risk of developing CVD so as to initiate early intervention to reverse poor prognisis (7). The ve interrelated components of MetS were connected by the core pathophysiology process, insulin resistance, which was related to a higher risk of CVD (23)(24)(25). Besides, a growing number of metabolic risk factors, such as low serum bilirubin levels(26), non-alcoholic fatty liver disease (NAFLD) (27), sarcopenia(28, 29) and hyperuricemia, have also been found relevant to the growing incidence of CVD.…”
Section: Discussionmentioning
confidence: 99%